1996
DOI: 10.1063/1.871648
|View full text |Cite
|
Sign up to set email alerts
|

Solitary kinetic Alfvén waves in the two-fluid model

Abstract: Employing the two-fluid model, a generalized Sagdeev equation governing solitary kinetic Alfvén waves (SKAWs) and the criterion for the existence of SKAWs, which are valid for different ranges of plasma pressure parameter β, are presented. In the limit cases of β≫me/mi and β≪me/mi, the present results correspond, respectively, with conclusions obtained by Hasegawa et al. [Phys. Rev. Lett. 37, 690 (1976)] and by Shukla et al. [J. Plasma Phys. 28, 125 (1982)], that is, SKAWs accompanied by, respectively, hump an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 9 publications
5
69
0
Order By: Relevance
“…The wave-particle interaction in KAWs depends sensitively on the plasma β parameter (Wu et al, 1996). Hasegawa and Cheng (1976) showed that in a low beta plasma 1 > β > m e /m i , the wave is weakly damped due to ion Landau damping leading to ion heating (Hasegawa and Cheng, 1976), whereas if electron temperature is comparable to ion temperature, nonlinear Landau damping occurs.…”
Section: Damping Of Kinetic Alfvén Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The wave-particle interaction in KAWs depends sensitively on the plasma β parameter (Wu et al, 1996). Hasegawa and Cheng (1976) showed that in a low beta plasma 1 > β > m e /m i , the wave is weakly damped due to ion Landau damping leading to ion heating (Hasegawa and Cheng, 1976), whereas if electron temperature is comparable to ion temperature, nonlinear Landau damping occurs.…”
Section: Damping Of Kinetic Alfvén Wavesmentioning
confidence: 99%
“…Zhao et al (2011) discussed the damping mechanism of KAWs in the dense plume structure of coronal holes and showed that KAWs are strongly damped in this region due to Landau damping when λ e k ⊥ < 0.3. Wu and Fang (1999 and Wu et al (1996) showed that the parallel electric field of the KAW can lead to effective electron heating due to kinetic damping or Ohmic dissipation, which can further dissipate the KAW energy to sustain the temperature of the coronal loop plasmas. This dissipation occurs due to the parallel electric field of the KAW, which helps the local electron heating and acceleration mechanism to balance the additional radiative loss of the bright plume.…”
Section: Damping Of Kinetic Alfvén Wavesmentioning
confidence: 99%
“…In a three-component plasma (electrons, protons, and heavy ions) magnetized by a magnetic field B 0 along the z axis, the equation set governing the dynamics of KAWs consists of the following (Wu et al 1995(Wu et al , 1996Wu & Chao 2004b): (i) the continuity equations of electrons, protons, and heavy ions…”
Section: Nonlinear Interaction Of Heavy Ions With Kawmentioning
confidence: 99%
“…Wu et al (1995) first derived an exactly analytical solution of SKAWs with an arbitrary amplitude in a low-β plasma with β/2 Q. Taking the cold ion approximation of T i T e , Wu et al (1996b) extended the works of Hasegawa and Mima (1976) (for α 1) and Shukla et al (1982) (for α 1) to more general ranges for the parameter α and took account of both the electron temperature and inertia terms simultaneously. They obtained a generalized Sagdeev equation and found a general criterion for the existence of SKAWs.…”
Section: Introductionmentioning
confidence: 99%